The mysterious human heart. 2, The spark of life [videorecording (DVD)] - Murdock, David (Ambrose Video, 2007)
Each of the three programs that make up "The mysterious human heart focuses on a different aspect of what we thought we knew, what we know now, and what we're on the verge of learning about the heart. This material is presented through the real-life dramas of people who suddenly learn that a normal, functioning heart is not something that can be taken for granted. In Episode 2, a look at the physiological electrical mechanism that keeps a heart beating regularly and efficiently and what happens when this most essential rhythm of life goes awry.